Ballistic trauma patients have decreased early narcotic demand relative to blunt trauma patients: Blunt ballistic injury opioid use. Issue 5 (May 2021) - Tucker, Douglass W.; Homere, Andrew J.; Wier, Julien R.; Bougioukli, Sofia; Carney, John J.; Wong, Monica; Inaba, Kenji; Marecek, Geoffrey S.
Highlights: Patients with ballistic fractures had fewer overall orthopaedic operative procedures and undergo these procedures sooner. During the 24 hours after definitive fixation, those with ballistic fractures utilized less opioids by MEU. In all other studied inpatient timepoints, there were no differences in opioid consumption by MEU. Abstract: Objectives: Blunt and ballistic injuries are two common injury mechanisms encountered by orthopaedic traumatologists. However the intrinsic nature of these injures may necessitate differences in operative and post-operative care. Given the evolving opioid crisis in the medical community, considerable attention has been given to appropriate management of pain; particularly in orthopaedic patients. We sought to evaluate relative postoperative narcotic use in blunt injuries and ballistic injuries. Design: Retrospective Cohort Study. Setting: Academic Level-1 Trauma Center. Patients: 96 Patients with blunt or ballistic fractures. Intervention: Inpatient narcotic pain management after orthopaedic fracture management. Main outcome measurements: Morphine equivalent units (MEU). Results: Patients with blunt injuries had a higher MEU compared to ballistic injuries in the first 24 hours postoperatively (35.0 vs 29.5 MEU, p=0.02). There were no differences in opiate consumption 24-48 hours (34.8 vs 28.0 MEU),  48 hours - 7 days post op (28.4 vs 30.4 MEU) or the 24 hours before discharge (30.0 vs 28.6 MEU). On multivariate analysis, during the 24-48 hours and 24 hours before discharge timepoints total EBL was associated with increased opioid usage. During days 3-7 (p<0.001) and in the final 24 hours prior to discharge (p=0.012), the number of orthopaedic procedures was a predictor of opioid consumption. Conclusion: Blunt injuries required an increased postoperative narcotic consumption during the first 24 hours of inpatient stay following orthopedic fracture fixation. However, there was no difference at other time points. Immediate post-operative pain regimens may be decreased for patients with ballistic injuries. Level of evidence: III.